Motion Compensation for Near-Range Synthetic Aperture Radar Applications - Wu, Huaming (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2012)
The work focuses on the analysis of influences of motion errors on near-range SAR applications and design of specific motion measuring and compensation algorithms. First, a novel metric to determine the optimum antenna beamwidth is proposed. Then, a comprehensive investigation of influences of motion errors on the SAR image is provided. On this ground, new algorithms for motion measuring and compensation using low cost inertial measurement units (IMU) are developed and successfully demonstrated.